Erythema Nodosum in Pregnancy - Kholoud A. Ghamri; Kara Nerenberg (Journal of King Abdulaziz University: Medical Sciences, 2023)
Erythema nodosum is a condition characterized by erythematous, tender and nonulcerating nodules (usually in a pretibial location) that can occur during pregnancy. While the pathophysiology often represents late hypersensitivity reaction to antigens associated with infections, certain medications and medical conditions as well as pregnancy itself can be the cause. The following case details a pregnant woman’s clinical course and diagnosis of Lofgren’s syndrome (triad of erythema nodosum, bilateral hilar adenopathy and polyarthritis).